THE EVOLUTION OF THE ALLIANCE CONCEPT IN CYBERSPACE: A CONCEPTUAL REVIEW - YILMAZ, Onur (Cyberpolitik Journal, 2025)
The classical realist approach considers the multi-actor, borderless, and hyper-anarchic nature of cyberspace. Supported by a qualitative literature review, the analysis shows that states cannot alone deter and neutralize cyber threats; therefore, flexible cooperation mechanisms involving the public sector, private companies, and international organizations have become essential. The key to enabling such cooperation is developing a new and broader definition of alliance that goes beyond traditional security theories. In this context, the study aims to contribute to the literature by examining the concept of cyber alliance and its characteristics, which cannot be explained through classical security paradigms.